Evaluation of the sternal intraosseous route as alternative emergency vascular access for the dental office: a manikin and cadaver model pilot study - Erdmann, Lara; Doll, Sara; Ihle, Brit; Kirsch, Joachim; Mutzbauer, Till Sebastian (Oral surgery, oral medicine, oral pathology and oral radiology, 2013)
Objective - To evaluate 2 sternal intraosseous access devices as alternatives to emergency intravenous access for dentists, using a manikin and a cadaver model. - Study Design - A group of 37 students performed a sternal intraosseous access on a manikin using a Vidacare kit including a puncture template and a prepuncture skin incision. Five months later, 9 of the students used the Vidacare and 8 used an Illinois needle (without template and incision) on adult human cadavers. India ink was injected as a tracer. - Results - Shorter times were recorded on cadavers compared with manikins in both systems. One Vidacare puncture ended subcutaneously. Two Illinois needle punctures perforated the sternum, one with intense mediastinal ink traces. Vidacare punctures took longer compared with Illinois needle punctures (medians, 32 vs 12 seconds; P = .0002). - Conclusions - Template use to identify the sternal puncture position, combined with additional prepuncture skin incision, may be more efficient and less predisposed to severe complications for dentists' emergency use.